THE CONSEQUENCES OF (DE)REGULATION ON EMPLOYMENT DURATION AND EFFICIENCY: AN EXPERIMENTAL STUDY. - BERNINGHAUS, SIEGFRIED; BLEICH, SABRINA; GÜTH, WERNER (Economic Inquiry, 2013)
If the future market wage is uncertain, engaging in long-term employment is risky, with the risk depending on how regulated the labor market is. In our experiment long-term employment can result either from offering long-term contracts or from repeatedly and mutually opting for rematching. Treatments differ in how regulations restrict the employer's flexibility in adapting the employment contract. All treatments allow for longer contract duration as well as for mutually opting to be rematched. Effort is chosen by employees after a contract is concluded. Treatments vary from no contract flexibility to no restriction at all. Will more (downward) flexibility be used in ongoing employment but reduce labor market efficiency? And will regulation crowd out long-term employment, in the form of long-term contracts or voluntary rematching?